Development of a low-fat, high-fibre snack: effect of bran particle sizes and processing conditions - Onipe, Oluwatoyin Oladayo (Heliyon, 2019)
The influence of fine and medium wheat bran (WB) particle sizes on process and quality parameters of a cereal fried dough (magwinya) was investigated. Magwinya is a snack that resembles, but different from doughnut and it is commonly consumed in most Sub-Saharan African countries. The effect of WB, fermentation and frying time was investigated on weight, diameter, volume, colour, hardness, fat, ash, and moisture, contents of magwinya. Further investigation on mineral and fibre contents as well as the consumer acceptance of optimised samples was also carried out. Predictive models were generated from responses with all lack of fit values >0.1, R(2) values ≤0.99 and desirability function of 0.82 and 0.78 for fine and medium WB, respectively. Close agreement between experimental and predicted values for fat and ash was found. The linear, quadratic and interaction effects of process variables significantly (p < 0.05) increased ash, hardness, lightness and moisture and reduced volume and fat content of magwinya. incorporation of 15 g WB, dough fermentation time of 71.66 min (fine WB) and 76.43 min (medium WB) and 3 min frying time significantly (p < 0.05) reduced fat content of magwinya by 44.96% and 22.92%, respectively, and increased ash by 50.41% and 54.20%, respectively. Fine WB resulted in the least fat content while medium WB increased the ash and minerals.